KONSEP PERNIKAHAN BERSAMAAN DALAM PERSPEKTIF HUKUM ISLAM DAN KEPERCAYAAN MASYARAKAT (STUDI DI KECAMATAN ULAWENG) - Erzy Aurelia Maharani; Syahabuddin; Lukman Arake; Hamzah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the botting massamang tradition in Ulaweng Subdistrict, Bone Regency, from the perspectives of community beliefs and Islamic law. This tradition involves the simultaneous celebration of multiple weddings within a single family and continues to spark debate; some members of the community view it as a taboo that can disrupt family harmony, while others regard it as a social custom that does not conflict with Islamic law. This study employs a qualitative method using a case study approach, incorporating sociological, normative theological, and phenomenological perspectives through observation, interviews, and documentation. The findings reveal differing viewpoints influenced by levels of religious understanding and adherence to local customs. In Islamic law, this practice is permitted as long as the pillars and conditions of marriage are fulfilled; however, the belief that it brings bad luck without evidence constitutes superstition that needs to be corrected. Thus, botting massamang can be understood as a valid custom (urf shahih) if it brings benefits, and as a corrupt custom (urf fasid) if it contradicts the principle of tawhid.